Capital Budgeting Analysis with the Timing of Events Uncertain. - Greer, Willis R. (The Accounting Review, 1970)
During the preparation of a capital budgeting study the decision-maker frequently encounters a situation where the timing of an important economic event is subject to uncertainty. Most typical of this class of problem is one in which doubt exists as to the useful life of a proposed machine. The analyst is aware that the associated revenue stream will come to an end at some future time, but it is not often that this time can be specified exactly. Similar characteristics are present in the uncertain timing of a research and development project's pay-off period and in the time lag between an advertising expenditure and the resulting increase in revenue. Several different approaches are now taken in facing the problem of uncertain timing. One common method is to treat the decision-maker's estimate of the most likely time as though it were certain. This estimate may be derived through a careful subjective probability analysis or simply from an intuitive feeling. If, greater precision is needed for some special application, there are two alternatives to the laborious task of computing the probabilities by hand. Those who have access to a digital computer will find it well worth while to write or otherwise obtain a program to produce probabilities.